Plan de marketing para mejorar el desarrollo comercial de la empresa Siderperú en la región Lambayeque. - Olazo Caballero, Víctor Estuardo (2010)
The present investigation deals with the application of a Plan of Marketing for company SIDERPERU, located in the Lambayeque region. The application of this Plan of Marketing looks for to improve the commercial development of the company, dice the sector in which it develops, and that is affected of favorable and unfavorable way, by the changing world of the globalization, still more considering that must take advantage of the opportunities business that offers the sector of the construction in the country.